Indigenous Peoples' Economic Empowerment Model as a Strategy in Accelerating National Economic Development: Case Study of Betawi Adat, Sundanese and Aceh Adat - Junaedi, I Wayan Ruspendi; Damayana, I Wayan; Waruwu, Dermawan; Utama, I Gusti Bagus Rai (Technium Social Sciences Journal, 2020)
Customary-based economic institutions aim to maintain the local wisdom of the community and accelerate national economic development. The economic life of the community has increased welfare through the empowerment of their customs. In the first year (2019) conducted research on indigenous peoples in 3 provinces: Bali which succeeded in developing the Village Credit Institution (LPD), the Batak indigenous people in North Sumatra succeeded in developing CU Ate Keleng, and the indigenous Dayak people in Central Kalimantan succeeded in developing CU Betang Asi. In the 2nd year (2020) conducted research on the indigenous peoples of 3 provinces: Betawi in DKI Jakarta which succeeded in developing the service cooperative "Jakarta Tentram Sejahtera", the Sundanese indigenous people in West Java succeeded in developing the North Bandung Cattle Breeders Cooperative (KPSBU) Lembang and Social Entrepreneurship The Big Price Cut Group, and the Acehnese indigenous people in Aceh have succeeded in developing the economy with the Baitulmal concept. With this business sector, it can empower indigenous peoples and at the same time improve the economy and welfare of their people. The empowerment of indigenous peoples is based on the concept that every member of the community has an obligation to support their respective customary activities. The customary institutions or types of businesses that exist in each location of this research aim to make it easy for the community to get capital in developing their respective businesses and in selling their products. With the existence of this financial institution, indigenous people experience an increase in their economy and welfare. To achieve this goal maximally and to find a model of economic empowerment for indigenous peoples that can be used as a model for the economy throughout Indonesia, in the 3rd year (2021) research will be continued in the Provinces of Maluku, West Sumatra, and South Sulawesi. In general, this research aims to produce an economic model for indigenous peoples as a strategy to accelerate national economic development. Specific objectives: To find out how indigenous peoples develop their economic systems; to identify forms of economic institutions for indigenous peoples in Indonesia, and to formulate a model for the economic empowerment of indigenous peoples as a strategy for accelerating national economic development. Researchers used qualitative and quantitative descriptive methods (mixed method) with a comparative case study type. Thus, this research is expected to obtain a model in order to accelerate national economic development. Data were collected and analyzed by means of observations, interviews, and documents. The mandatory output of this research is the economic model of indigenous peoples.